2017
DOI: 10.1038/srep45395
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and NF-κB are Simultaneously Suppressed in Dendritic Cells in Lung Cancer

Abstract: Tumour-induced dendritic cell (DC) dysfunction plays an important role in cancer immune escape. However, the underlying mechanisms are not yet fully understood, reflecting the lack of appropriate experimental models both in vivo and in vitro. In the present study, an in vitro study model for tumour-induced DC dysfunction was established by culturing DCs with pooled sera from multiple non-small cell lung cancer (NSCLC) patients. The results demonstrated that tumour-induced human monocyte-derived DCs exhibited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 56 publications
(67 reference statements)
1
22
0
1
Order By: Relevance
“…(TLR)-induced proinflammatory mediators (Park et al, 2004;Kitamura et al, 2005;Cheng et al, 2008;Melillo et al, 2010;Wölfle et al, 2011); and 5) increased tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase and resultant T cell apoptosis mediated by kynurenine, a tryptophan metabolite (Barton, 2006). These STAT3 effects are mediated by pY-STAT3; inhibition of JAK/STAT3 signaling improves mature DC function and augments antitumor immunity (Nefedova et al, 2004(Nefedova et al, , 2005a, although attenuating STAT3 and NF-kB signaling in immature DCs leads to systemic DC dysfunction in non-small cell lung cancer (NSCLC) (Li et al, 2017). 4.…”
Section: Inhibition Clinicalmentioning
confidence: 99%
“…(TLR)-induced proinflammatory mediators (Park et al, 2004;Kitamura et al, 2005;Cheng et al, 2008;Melillo et al, 2010;Wölfle et al, 2011); and 5) increased tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase and resultant T cell apoptosis mediated by kynurenine, a tryptophan metabolite (Barton, 2006). These STAT3 effects are mediated by pY-STAT3; inhibition of JAK/STAT3 signaling improves mature DC function and augments antitumor immunity (Nefedova et al, 2004(Nefedova et al, , 2005a, although attenuating STAT3 and NF-kB signaling in immature DCs leads to systemic DC dysfunction in non-small cell lung cancer (NSCLC) (Li et al, 2017). 4.…”
Section: Inhibition Clinicalmentioning
confidence: 99%
“…Human peripheral blood mononuclear cells (PBMCs) were isolated from the peripheral blood of healthy donors at the Blood Centre of Anhui Province using Ficoll–Hypaque (Solarbio, P4350) density gradient centrifugation NK cells in PBMCs were further purified using human NK Cell Isolation Kit (Miltenyi Biotec, 130‐092‐657) following manufacturer's instructions (purity >95%). Isolated NK cells were cultured in RPMI medium supplemented with 10% FBS, penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…These results showed that DEIRGs in prediction model could act as predictor for predicting immunocyte infiltration in LUSC. A study demonstrated that STAT3 and NF-κB signaling pathways were simultaneously attenuated in dendritic cells of lung cancer (48). A study showed that the tumor-associated CD66b neutrophils were correlated with adverse prognostic factors of NSCLC (49).…”
Section: Discussionmentioning
confidence: 99%